The protean music career as a sociopolitical orientation : The mutually integrated, non-hierarchical work values of socially engaged musicians - Westerlund, Heidi; Karttunen, Sari (Sage, 2024)
Socially engaged, participatory music making is slowly establishing itself as a complement to musicians’ portfolio careers, although it may still be considered of less value than established concert hall practices. To gain a better understanding of the drivers toward socially engaged practice in music field, we analyzed 20 semi-structured interviews with musicians in Finland, using the lenses of work values and career orientations. The abductive, theoretical reading analysis shows that the musicians viewed the social-relational nature of their work as a fundamental feature of the practice and sought congruence between their work values and other personal values. The interviewees renounced the hierarchy between intrinsic (autonomy, creativity, variety, achievement, challenge, and intellectual stimulation) and social work values (interacting with people, altruism, and contribution to society), and found participatory practice to be artistically freeing and personally rewarding. Their work appeared less driven by extrinsic values (economic gain and status); hence, their self-directed and values-driven orientation resonates strongly with the notion of the protean career. Although their sociopolitical stance involved the risk of weakening their professional status and they had to constantly justify their work amongst their colleagues, they all expressed conscious counternarratives to what they considered the elitism of expert culture in traditional music institutions. The study argues that the practice of socially engaged musicians can help the professional field of music reconsider and transform its stubborn value hierarchies in the complex social, political, ethical, and moral landscapes of contemporary society.
Keywords: muusikot; professionalismi